Kedudukan Perempuan Bali Terhadap Harta Bersama Dalam Hal Terjadi Perceraian (Analisis Perkembangan Yurisprudensi)*) - Sukranatha, A.A. Ketut (Jurnal Studi Jender SRIKANDI; Vol. 5, No. 1 Januari 2005)
This study aims at finding out the jurisprudence development on the effect of divorce toward the status of mutual property in the marriage (gunakarya). The study is conducted by using normative approach that is to study the judge decision at Denpasar Court of First Instance that related to the mutual property dispute.Results of the study indicate that the judge decision (jurisprudence) on the effect of divorce toward the status of mutual property has experienced some depelovment. In the past (in the period of Kertha Raad Custom Court), the status of mutual property after divorce was judged based on the guilty one in the divorce. If the divorce was caused by guiltiness commited by the wife, the mutual property was shared together with 1/3 for the wife and 2/3 for the husband. Recently the judge decisions (jurisprudence) have changed, namely if there is mutual property dispute after the divorce the Court always decides that the mutual is shared equally (½ : ½) between the (former) husband and the (former) wife without considering who is the guilty one in the divorce.This normative study needs to be continued with emprical study so that the status of mutual property after the divorce can be indentified if the mutual property dispute is settled outside of the Court.
Keywords: perceraian, harta bersama, yurisprudensi